Analyzing the Determinants of Employee Work Discipline: An Empirical Study of Administrative Staff - Ni Dwi Fefiyani Subawa; Komang Krisna Heryanda; M. Rudi Irwansyah (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
Work discipline constitutes a fundamental element in ensuring the effectiveness and accountability of human resource management within higher education institutions. In developing academic units, inconsistencies in attendance patterns and working-hour compliance indicate that disciplinary behavior remains a managerial concern. At the Faculty of Medicine, Universitas Pendidikan Ganesha, fluctuations in digital attendance records and accumulated working-hour deficits suggest the need to examine behavioral and organizational determinants shaping employee discipline. This study aims to analyze the influence of motivation, Work Culture, and leadership style on the work discipline of administrative staff, both partially and simultaneously. A quantitative approach was employed using a saturated sampling technique involving all 45 administrative employees. Data were collected through a structured Likert-scale questionnaire and supported by institutional attendance records. Instrument validity and reliability were confirmed before analysis, and multiple linear regression was applied to test the hypotheses. The findings reveal that motivation and Work Culture have positive and significant effects on work discipline, whereas leadership style does not show a significant partial effect. However, collectively, the three variables significantly explain variations in employee discipline. These results underscore the importance of strengthening motivational practices and cultivating a supportive Work Culture to foster sustainable disciplinary behavior in public higher education settings.